Using a social-ecological systems approach to investigate hillslope seep wetlands ecosystem structure and functionality in the Tsitsa River catchment, Eastern Cape, South Africa - Libala, Notiswa (Rhodes University, Faculty of Science, Institute for Water Research, 2019)
Wetlands are critical ecosystems that can provide services of great social, economic and environmental value to the society. Yet, in South Africa, hillslope seep wetlands are among the most threatened ecosystems due to human-induced activities and are disappearing rapidly. Further, despite the potential vulnerability of hillslope seep wetland to disturbances, and their criticality in relation to all year round provision of forage for livestock grazing, they are among the most poorly studied wetland systems. Using a social-ecological system framing, and drawing on a range of ecological and social sciences methods, this study shed light on ways in which an integrative approach can contribute to sustainable utilisation of hillslope seep wetlands in the Tsitsa River catchment in the Eastern Cape province of South Africa. The study specific objectives were to i) evaluate the performance of Floristic Quality Assessment Index (FQAI), WET-Health and Floristic Assessment Quotient for Wetlands Index (FQAWet) indices for assessing hillslope seep wetlands ecological health ii) develop a trait-based approach for assessing the potential resilience and vulnerability of hillslope seep wetland plant species to disturbances, iii) assess the role of hillslope seep wetlands in the local communities in relation to livestock, and explore understanding of local people about the value of hillslope seep wetlands, iv) demonstrate collaborative insights emerging from an integrative social-ecological system research process to inform sustainable management of hillslope seep wetlands. A total of 11 hillslope seep wetlands were visually classified based on the level of erosion. Plant species composition within the wetlands was determined along a 100 m line transects across the hillslope wetland sites. 5 quadrats of 0.2m2 were also placed along transect for vegetation collection and cover. The plant species collected were used to calculate (FQAI) and FQAWet scores to evaluate the condition of hillslope seep wetlands. The degree of human disturbances was assessed using the Anthropogenic Activity Index (AAI), an index for qualitatively assessing the degree of human disturbance based on visual inspection of a wetland site. Factors represented in the AAI, include: (i) surrounding land use intensity; (ii) soil disturbance; (iii) hydrological alteration; (iv) habitat alteration within wetland; (v) vegetation community quality. The vegetation samples were collected in summer 2016 and winter 2017. All assessed indices were regressed against AAI to evaluate their performances. All assessed indices FQAI, FQAWet and WET-Health showed that hillslope seep wetland were impacted by human activities. FQAIall and WET-Health showed the strongest response to AAI in winter, while FQAIdom and FAQWet showed a weak response to AAI in all seasons. Overall, the findings of this study suggest that FQAIall and WET-Health are potentially better tools for assessing the biological conditions of hillslope seep wetland in South Africa. A novel trait-based approach was developed using seven plant traits and 27 trait attributes. Based on the developed approach, plant species were grouped into three potentially vulnerable groups in relation to grazing pressure. It was then predicted that species belonging to the highly vulnerable group would be less dominant at the highly disturbed sites, as well as in the winter season when grazing pressure is at its highest. The result corresponds largely with the seasonal predictions; however this was not the case for sites. The approach developed in this study worked and it was useful for predicting the potential responses of plant species in hillslope seep wetlands to grazing pressure. The success of the approach seasonally could be attributed to the careful selection of the traits, reflecting the mechanistic relationship between the grazing mode of stress on vegetation and trait-mediated biotic response. However, this still need to be refined using accurate vegetation cover methods that might have had impact on the lack of correspondence within sites. The results of the present study revealed that communities largely perceive hillslope seep wetlands as important ecosystems for their livelihoods. They recognise that the importance stems from services provided by the wetlands, particularly for livestock grazing during the dry season. Although hillslope seep wetlands are viewed as important ecosystems for livelihoods, the communities also perceive these wetlands as highly eroded ecosystems. Community members indicate willingness to strengthen local natural resource governance systems, which could lead to better management of hillslope seep wetlands. A range of protective strategies for hillslope seep were suggested by community members, including fencing, active herding and rotational grazing. The study suggests that active involvement of local communities is critical to the successful management of natural resources. The study highlights the need to consider the role of local people as influential components within social-ecological systems in order to promote effective management and conservation interventions of hillslope seep wetlands. Overall, the study highlights the criticality of an integrative social-ecological system approach for holistic management of hillslope seep wetlands within the studied catchment.
Keywords: Wetland management -- South Africa -- Eastern Cape; Wetland ecology -- South Africa -- Eastern Cape; Wetland conservation -- South Africa -- Eastern Cape; Slopes (Physical geography) -- South Africa -- Eastern Cape; Vegetation management -- South Africa -- Tsitsa River Catchment; Land degradation -- Control -- South Africa -- Tsitsa River Catchment; Grazing -- Environmental aspects -- South Africa -- Tsitsa River Catchment; Ecosystem management -- South Africa -- Tsitsa River Catchment; Wetland plants -- Effect of grazing on